PERMINTAAN PANGAN HEWANI RUMAH TANGGA DI PROVINSI JAWA BARAT - Endah Nora Susanti; Wiwiek Rindayati; Sahara Sahara (IPB University, 2014)
Indonesian’s consumption of food derived from animal products is relatively low. In general, the consumption behaviour depends not only on prices and total expenditure, but also on some household characteristics. Households with different characteristics have different spending patterns reflecting the level of welfare of each household. This study analyzed the food consumption of households using the LA system (AIDS) of five groups of animal based food. The data used in this research are the National Socio-Economic Survey (NSES) in 2012 in West Java Province. The result show that the consumption of animal based food is influenced by household income and also by other factors including socio-demographic household size, type of area and level of education of household head. The value of own price elasticity showed that all commodities are inelastic. Based on the values of cross elasticity, all animal based food commodities are complement to each other except that fish are substitutes for eggs. Fish and egg are categorized as normal good, whereas meat, poultry and milk are categorized as luxury goods. Key words: food consumption, animal based food, AIDS, elasticity